The role of HIV/AIDS disability grants in influencing people living with HIV to adhere to antiretroviral therapy with specific reference to the South African Red Cross Society in Nyanga - Ndlumbini, Ntombencane Margaret (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil. (Industrial Psychology))--University of Stellenbosch, 2009.